Rhode Island's Tragic Era - Quirk, Charles (Relations industrielles / Industrial Relations, 1952)
SummaryThis article is only a short extract from an interesting study on the employment problems of Rhode Island from 1935-1950; it has as objective to make known to the reader the historical and economic evolution of the textile industry in Rhode Island. The author describes the competition which arose between the North and the South; very unimportant at the beginning, it increased afterwards to take on disastrous proportions and bring about fatal consequences: decrease in productivity, migration of the mills to the South and general unemployment. The history of the textile industry of New England furnishes an example of a system conforming to the "laissez-faire" of free capitalism: the seeking of the highest possible profit without worrying about social responsibility. This system must be subjected to the ethics of business or destroy itself.